Differential substrate degradation by super-degron: EGFP in wild-type mouse cells, PD-1 requires CRBN humanization - Chie Naruse; Ojiro Ishibashi; Masatoshi Ohgushi; Hirohiko Imai; Tomoko Matsuzaki; Xuchi Pan; Tatsuhiko Miyazaki; Yuka Shidahara; Yu Shirakawa; Fumihiro Sugiyama; Masahide Asano (iScience)
Summary: Protein knockdown using a zinc finger degron tag and thalidomide analogs was previously considered ineffective in mouse cells. However, using EGFP as an indicator, we found that a super-degron tag (SD) enables degradation in mouse cells when combined with iberdomide or mezigdomide. While SD-tagged EGFP was degraded in wild-type mouse cells, SD-tagged PD-1 required human-type CEREBLON (CRBNI391V) for degradation. In mice with CRBNI391V, endogenous PD-1 tagged with SD was efficiently degraded in T cells both in vitro and in vivo. Compared with anti-PD-1 antibody treatment, the degradation of PD-1 led to more rapid activation of CD8+ T cells. Moreover, pomalidomide that crosses the brain-blood barrier reduced PD-1 expression in the brain. These results suggest that SD and thalidomide analogs can be used for in vitro and in vivo protein knockdown in mice, although some conditional settings are required.